Existentialist Feminism in Barbie Movie (John Fiske Semiotics Study) - Pienrasmi, Hanindyalaila; Amalia, Nurfat; Verawati, Noning; Poyo, M. Denu (Al Huwiyah: Journal of Woman and Children Studies, 2024)
Abstract Existentialist feminism highlights the importance of individual freedom and personal responsibility, and emphasizes women’s struggle in the domestic sphere. The Barbie film is the subject of this research because it can depict and educate about issues of gender equality and feminism to the audience, especially young girls, with strong characters and stories, and has become a symbol that has grown with society. This research aims to understand the ideas of existentialist feminism that are represented and visualized in the Barbie film according to John Fiske's semiotic analysis. The analysis found that this film shows the values of existentialist feminism primarily through aspects of costume, narrative, appearance, conflict, behavior, and music in certain scenes. The most frequently appearing value is supporting women's freedom in constructing themselves.Keywords: Feminism Film Barbie , Women.   AbstrakFeminisme eksistensialis menyoroti pentingnya kebebasan individu dan tanggung jawab pribadi, serta menekankan perjuangan perempuan dalam ranah domestik. Film Barbie menjadi objek penelitian ini karena mampu menggambarkan dan mengedukasi tentang isu-isu kesetaraan gender dan feminisme kepada penonton, terutama anak-anak perempuan, dengan karakter dan cerita yang kuat serta menjadi simbol yang telah tumbuh bersama masyarakat. Penelitian ini bertujuan untuk mengetahui ide feminisme eksistensialis yang di representasikan dan divisualisasikan dalam film Barbie menurut analisis semiotika John Fiske. Hasil analisis menemukan bahwa film ini menunjukkan nilai feminisme eksistensialis terutama melalui aspek kostum, narasi, penampilan, konflik, perilaku, dan musik dalam adegan-adegan tertentu. Nilai yang paling sering muncul adalah mendukung kebebasan perempuan dalam mengkonstruksi dirinya sendiri.Keywords: Feminisme, Film Barbie, Perempuan.